2014
DOI: 10.1155/2014/815984
|View full text |Cite
|
Sign up to set email alerts
|

Simple Measures of Function and Symptoms in Hospitalized Heart Failure Patients Predict Short-Term Cardiac Event-Free Survival

Abstract: Background. Heart failure (HF) is a prevalent chronic condition where patients experience numerous uncomfortable symptoms, low functional status, and high mortality rates. Objective. To determine whether function and/or symptoms predict cardiac event-free survival in hospitalized HF patients within 90 days of hospital discharge. Methods. Inpatients (N = 32) had HF symptoms assessed with 4 yes/no questions. Function was determined with NYHA Classification, Katz Index of Activities of Daily Living (ADLs), and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…In patients with HF, a low BMI is known to reduce readmission [ 16 ]. Additionally, the poor NYHA class is associated with readmission within 90 days [ 17 ]. Anemia in patients with HF is a predictor of readmission within 90 days [ 9 , 18 ], and their low hemoglobin levels are likely to result in readmission because of heart load [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with HF, a low BMI is known to reduce readmission [ 16 ]. Additionally, the poor NYHA class is associated with readmission within 90 days [ 17 ]. Anemia in patients with HF is a predictor of readmission within 90 days [ 9 , 18 ], and their low hemoglobin levels are likely to result in readmission because of heart load [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigators did find in a group of hospitalized HF patients that dyspnoea did predict short-term cardiac event-free survival. 25 Another group of investigators found that survival rates were improved with diary use that included daily body-weight monitoring, but hospital readmission rates were not reported. 26 Our data show that increases in dyspnoea for 14 days did confer an increased risk for an office visit.…”
Section: Heart Failure Signs and Symptomsmentioning
confidence: 99%
“…1,2 Fatigue and dyspnea, hallmark symptoms of HF, contribute to a significant reduction in quality of life and are indicators of HF severity and worsening prognosis. 2,3 Functional status is considered an important outcome of HF as it describes the impact of HF symptoms on patient’s daily physical function. 3,4 Functional status is an important clinical consideration in HF management.…”
mentioning
confidence: 99%